Latest development of radiokrypton dating – A tool to find and study paleogroundwater. (10th May 2020) - Jiang, Wei; Hu, Shui-Ming; Lu, Zheng-Tian; Ritterbusch, Florian; Yang, Guo-min
Abstract: The study of paleogroundwater on a timescale of several thousands to a million years is interesting both in terms of understanding the aquifer system itself and water resource management. It may also provide valuable information about the paleoclimate. In their seminal work, Loosli and Oeschger (1969) identified 81 Kr as an ideal age tracer for paleogroundwater up to one million years old. Since then radiokrypton dating has been a desirable tool. Recent developments in the Atom Trap Trace Analysis method have made radiokrypton dating available to the earth science community at large. In this paper we will show the current status for radiokrypton dating with an emphasis on sample size reduction. The latest advancements have allowed analysis with only 20 kg of water. Moreover, we will review selected studies that have been carried out on some large aquifers with old groundwater around the world using this new tool.